Application of the Utaut Model to the Crowdfunding-Based Halal Tourism Capital Platform Innovation - Ricky Dendi Oktavian; M Ruslianor Maika (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
The lack of budget in developing halal tourism in Indonesia encourages researchers to find innovative solutions. This study aims to determine respondents' views on the plan to build a halal tourism capital platform. This study used a qualitative method by applying a phenomenological approach to gather information from respondents based on their experiences. This study's results are divided into four categories, namely performance expectancy, effort expectancy, social influence, and facilitating conditions presented in the form of a network to combine each answer in each category. The conclusion obtained from this study is that in the variety of performance expectations, the respondents agreed on the halal tourism capital platform's innovation. The respondents felt the ease with the halal tourism capital platform's design in the effort expectancy category. In the social influence category, respondents expressed their interest and interest in using the halal tourism capital platform's innovation by providing suggestions for improving infrastructure and facilities that support the halal tourism capital platform's invention in the facilitating conditions category.